2014
DOI: 10.1378/chest.13-0708
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Nodule Volume in the Context of Malignancy Prediction for Small Pulmonary Nodules

Abstract: When faced with a patient with a pulmonary nodule, it is incumbent on the clinician to differentiate benign cases from cancer. Although most clinicians use clinical experience to estimate the probability of malignancy in pulmonary nodules, some rely on one or T he pulmonary nodule is a single, spherical, wellcircumscribed, radiographic opacity that measures , 3 cm in diameter and is completely surrounded by aerated lung. There is no associated atelectasis, hilar enlargement, or pleural effusion. 1 Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…In univariate analysis, we found that smaller tumor size and larger GGO proportion were significantly associated with indolent and less aggressive tumors. Similarly, there were several studies also found that the size and mass of the nodule are determinants of invasive adenocarcinoma (8,(16)(17)(18). While, recently an observation found that in patients with tumors smaller than 3 cm, DFS was significantly associated with solid tumor size, but not with whole tumor size in early stage tumors (9).…”
Section: Discussionmentioning
confidence: 86%
“…In univariate analysis, we found that smaller tumor size and larger GGO proportion were significantly associated with indolent and less aggressive tumors. Similarly, there were several studies also found that the size and mass of the nodule are determinants of invasive adenocarcinoma (8,(16)(17)(18). While, recently an observation found that in patients with tumors smaller than 3 cm, DFS was significantly associated with solid tumor size, but not with whole tumor size in early stage tumors (9).…”
Section: Discussionmentioning
confidence: 86%
“…MEHTA et al [36] added volumetric nodule measurement to an existing prediction model for nodule malignancy estimation, showing an increase in the number of nodules correctly classified. Notably, the study included only lesions <15 mm in diameter.…”
Section: Size Measurements: Methods and Limitationsmentioning
confidence: 99%
“…Next, the exact description of shape and size is important. The bigger the nodule, the higher the chance for malignant transformation [10,[27][28][29][30][31]. Likewise, information regarding location [30], growth [32] and shape [33] should be respected, too.…”
Section: Discussionmentioning
confidence: 99%